Review of linguistic approach in the workplace management research. Issue 1 (2014) - ,; ,
Abstract : Purpose – The purpose of this article is to review the use of linguistic methods such as narrative and discourse analysis in workplace management research.Design/methodology/approach – Ten journals are reviewed in a time period of six years between years 2004‐2010. The journals are categorized into three linguistic methodological journals and seven journals on built environment. Additionally articles were gathered with search words of workplace management, discourse and narrative analysis. Out of the total 2, 245 articles, 40 articles were considered to be relevant for this research.Findings – The linguistic methods of narrative and discourse analysis are not recognized in the workplace management research in a comprehensive way by combining the research on built environment to the research on organization and culture. In the workplace management research methods of narrative and discourse analysis were applied to the processes of built environment. Additionally methods were applied to the research of space and place as means of communication and means of identity construction.Practical implications – Linguistic approach would reveal underlying messages behind evident structures of workplace and give new insights on understanding and developing workplaces both in design and in use.Originality/value – The linguistic methods of narrative and discourse analysis are rarely used in workplace management research and should be considered as a new resource in the research of WPM.